Structure–activity relationship studies of [1, 2, 5]oxadiazolo[3, 4-b]pyrazine-containing polymyxin-selective resistance-modifying agents. (15th September 2022) - Dutta, Somnath; Liu, Nianzi; Gao, Yuefeng; Beck, Lily; Wang, Xiang
Graphical abstract: Abstract: Multidrug-resistant (MDR) Gram-negative bacteria are an urgent and rapidly spreading threat to human health with limited treatment options. Previously, we discovered a novel [1, 2, 5]oxadiazolo[3, 4- b ]pyrazine-containing compound (1 ) that selectively re-sensitized a variety of MDR Gram-negative bacteria to colistin, one of the last-resort antibiotic. Herein, we report the structure–activity relationship studies of compound 1 that led to the discovery of several more potent and/or less toxic resistance-modifying agents (RMAs). Further evaluation of these RMAs showed that they were effective in a wide range of MDR bacteria. These results demonstrated these compounds as a novel class of RMAs and may be further developed as therapeutic agents.